Loss of estrogen-related receptor alpha disrupts ventral-striatal synaptic function in female mice. (4th August 2016) - De Jesús-Cortés, Héctor; Lu, Yuan; Anderson, Rachel M.; Khan, Michael Z.; Nath, Varun; McDaniel, Latisha; Lutter, Michael; Radley, Jason J.; Pieper, Andrew A.; Cui, Huxing
Highlights: Loss of Esrra increases basal excitatory synaptic transmission in the ventral striatum specifically in female mice. Loss of Esrra decreases paired-pulse ratio in the ventral striatum specifically in female mice. Loss of Esrra reduces ventral-striatal synaptic pool density specifically in female mice. Loss of Esrra increases basal GluR1 phosphorylation at Ser 831 and Ser 845 . Abstract: Eating disorders (EDs), including anorexia nervosa, bulimia nervosa and binge-ED, are mental illnesses characterized by high morbidity and mortality. While several studies have identified neural deficits in patients with EDs, the cellular and molecular basis of the underlying dysfunction has remained poorly understood. We previously identified a rare missense mutation in the transcription factor estrogen-related receptor alpha (ESRRA) associated with development of EDs. Because ventral-striatal signaling is related to the reward and motivation circuitry thought to underlie EDs, we performed functional and structural analysis of ventral-striatal synapses in Esrra-null mice. Esrra-null female, but not male, mice exhibit altered miniature excitatory postsynaptic currents on medium spiny neurons (MSNs) in the ventral striatum, including increased frequency, increased amplitude, and decreased paired pulse ratio. These electrophysiological measures are associated with structural and molecular changes in synapses of MSNs in the ventral striatum, including fewer pre-synaptic glutamatergic vesicles and enhanced GluR1 function. Neuronal Esrra is thus required for maintaining normal synaptic function in the ventral striatum, which may offer mechanistic insights into the behavioral deficits observed in Esrra-null mice.